Super-hydrophobic / super-oleophylic degradable photo-thermal aerogel adsorption material and demulsification performance thereof

By using cellulose and chitosan as the framework and combining nanocarbon black and methyltrimethoxysilane modification technology, a degradable aerogel with vertical channel structure and photothermal properties was prepared, which solved the complex preparation of existing materials and environmental pollution, and achieved the effect of efficient adsorption of high viscosity crude oil.

CN119869489APending Publication Date: 2025-04-25GUANGXI UNIV

Patent Information

Application Number
CN202510244091.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing superhydrophobic/super-oilophilic aerogel materials have problems of high cost, complex processes and environmental pollution during the preparation and recycling process, and their adsorption capacity to high viscosity crude oil is insufficient.

Method used

Using cellulose and chitosan extracted from discarded cartons as organic frameworks, chemical crosslinking of glutaraldehyde and introducing nanocarbon black particles and methyl trimethoxysilane for hydrophobic modification, to prepare a degradable aerogel with vertical pore structure and photothermal properties.

Benefits of technology

It realizes a high mechanical performance aerogel with simple preparation, low cost and environmentally friendly, with excellent super-hydrophobic/super-oleophilicity and efficient adsorption capabilities, and shows excellent cleaning effect on high-viscosity crude oil and maintains stability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869489A_ABST
    Figure CN119869489A_ABST
Patent Text Reader

Abstract

The invention provides a super-hydrophobic / super-oleophylic degradable photo-thermal aerogel adsorption material and demulsification performance thereof, and belongs to the technical field of oil-water separation materials, and the super-hydrophobic / super-oleophylic degradable photo-thermal aerogel adsorption material is prepared by the following steps: (1) extracting cellulose from waste cartons and performing ultrasonic dispersion to prepare a cellulose suspension; (2) preparing a chitosan solution; (3) mixing the cellulose suspension and the chitosan solution to obtain a cellulose / chitosan composite solution, adding nano carbon black particles, glutaraldehyde and a methyltrimethoxysilane aqueous solution into the cellulose / chitosan composite solution, and stirring; (4) injecting the mixed solution into a mold, and performing directional freezing on a semiconductor refrigeration platform; and (5) performing freeze drying on the frozen sample, and then putting the frozen sample into a drying oven for cross-linking to obtain the aerogel. The aerogel is obtained by taking cellulose extracted from waste cartons and chitosan as organic frameworks, carrying out chemical crosslinking through glutaraldehyde, introducing nano carbon black particles as photo-thermal components and carrying out hydrophobic modification through methyltrimethoxysilane, and has an excellent pore structure, super-hydrophobicity-super-lipophilicity and excellent mechanical properties; the adsorbent has efficient adsorption capacity on high-viscosity crude oil; and the device can be repeatedly used and is biodegradable, so that the burden on the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil spill adsorption materials, and in particular to a degradable photothermal aerogel with super hydrophobicity / super oleophilicity and its oil spill adsorption performance. Background Art

[0002] The rapid development of the oil extraction industry has promoted economic prosperity, but oil spill accidents such as oil pipeline leakage and tanker collisions have occurred frequently, bringing catastrophic damage to the ecology and economy. Traditional methods such as mechanical skimmers, in-situ combustion and bioremediation often involve high energy consumption and secondary pollution. Therefore, the use of adsorbents with superhydrophobicity / superoleophilicity for oil and water as separation materials is a prominent measure. It has been reported that superhydrophobic / superoleophilic 3D porous absorbents based on cotton, sponges and metal foams have been used to clean up oil spills, but their adsorption capacity for low-viscosity oil is much lower than that of aerogels with higher porosity and lower density. Aerogels made of graphene oxide, carbon nanotubes or MXene with high specific surface area have excellent adsorption capacity. However, these materials have the following problems: high raw material cost, complex preparation methods, unsuitable for large-scale production; and aerogels will cause a recycling burden after reaching the end of their service life.

[0003] It is worth noting that the express delivery industry uses 26.503 billion tons of paper packaging boxes each year. Extracting cellulose (CL) from these discarded packages as a raw material for preparing aerogels can not only effectively utilize waste, but also significantly reduce the environmental burden. In addition, chitosan (CS) is a typical renewable material with biocompatibility and biodegradability. The molecular structures of these two materials contain hydroxyl, carboxyl and amino groups, which provide grafting sites for combining with other functional materials. From the perspective of low cost and environmental protection, designing a superhydrophobic / superoleophilic CL / CS-based aerogel with good compressibility will be a simple and low-energy method for crude oil adsorption. The viscosity of crude oil at room temperature is 10 3 -10 5 mPa s, accounting for 40% of the world's oil reserves. The viscosity of crude oil decreases with increasing temperature, so aerogels with thermal responsiveness are an effective solution to improve the diffusion coefficient of crude oil. Various superhydrophobic 3D porous absorbers wrapped by electrothermal or photothermal materials can reduce the viscosity of crude oil, thereby accelerating the absorption process. However, aerogels that rely on Joule heat or magnetocaloric heat to accelerate the flow of crude oil are limited in their widespread application due to high energy consumption during the absorption process and the need for complex energy input devices. Therefore, it is very advantageous to rely on clean energy such as solar energy to achieve crude oil adsorption. In summary, the development of a superhydrophobic aerogel with high mechanical properties that is simple to prepare, low cost, environmentally friendly, reusable and relies on clean energy is of great significance to meet the above challenges. Summary of the invention

[0004] The object of the present invention is to provide a photothermal super hydrophobic aerogel (PTBA) for crude oil recovery. The aerogel uses cellulose and chitosan extracted from waste cartons as an organic skeleton, is chemically cross-linked by glutaraldehyde, and introduces nano carbon black particles as a photothermal component. In addition, the aerogel is hydrophobically modified by methyltrimethoxysilane. The aerogel has the following excellent properties: simple preparation, low cost, environmentally friendly, reusable, vertical pore structure, high mechanical properties, biodegradability and flame retardancy.

[0005] Inspired by the pore structure of the stem of Taro, the present invention uses industrial products as modules and adopts the method of ice template directional freezing to construct a vertical pore structure with high mechanical properties. On this basis, PTBA is prepared by freeze-drying process in combination with the hydrophobic modification of nanoscale carbon black particles and methyltrimethoxysilane. The material has good superhydrophobicity, photothermal performance and mechanical strength, and shows excellent tolerance and stability in various extreme environments.

[0006] The PTBA of the present invention has excellent adsorption and cleaning performance, and can maintain good absorption and separation capabilities even after repeated use. In addition, when treating oil spills of different viscosities, PTBA can not only completely adsorb the spread oil film, but also show good adsorption capacity for high-viscosity crude oil.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a degradable photothermal aerogel with super hydrophobicity / super oleophilicity comprises the following steps:

[0009] (1) extracting cellulose from waste cartons and preparing a cellulose suspension by ultrasonic dispersion;

[0010] (2) preparing chitosan solution;

[0011] (3) mixing the cellulose suspension and the chitosan solution to obtain a cellulose / chitosan composite solution, adding nano carbon black particles, glutaraldehyde and methyltrimethoxysilane aqueous solution to the cellulose / chitosan composite solution, and stirring;

[0012] (4) injecting the composite solution into a mold and performing directional freezing on a semiconductor refrigeration platform;

[0013] (5) The frozen sample is freeze-dried and then placed in an oven for cross-linking to obtain an aerogel.

[0014] Furthermore, in step (1), the specific treatment process of the cellulose suspension is as follows: waste carton powder is treated with sodium hydroxide solution and sodium hypochlorite solution, washed with deionized water until neutral, then filtered, and ultrasonically dispersed to obtain a cellulose suspension; the concentration of the cellulose suspension is 0.5wt%.

[0015] Furthermore, in step (2), the specific process of preparing the chitosan solution is: adding chitosan powder to 1% acetic acid solution, and vigorously stirring at a temperature of 60° C. for 1 hour to obtain a chitosan solution; the concentration of the chitosan solution is 0.5wt%.

[0016] Furthermore, in step (3), the mass ratio of the nano carbon black particles to the cellulose is 0.1:1, the mass ratio of the glutaraldehyde solution to the chitosan is 0.04:1, and the volume ratio of the methyltrimethoxysilane solution to the total solution is 0.6:100.

[0017] Furthermore, in step (4), the specific conditions of the directional freezing are as follows: the surface temperature of the semiconductor refrigeration platform is -20°C, and the directional freezing is performed at room temperature;

[0018] Furthermore, in step (5), the freeze dryer is set at -50°C, 1Pa; the cross-linking temperature is 110°C, and the time is 2h.

[0019] During the cross-linking process, long-chain cellulose and chitosan molecules react with glutaraldehyde and methyltrimethoxysilane to form a continuous network structure, which significantly improves the integrity and strength of the overall structure.

[0020] Through the preparation method of the present invention, during the directional freezing process, cellulose and chitosan solutes will form vertical wall structures under the extrusion of ice crystals. After freeze drying, these wall structures are converted into vertical channel structures. This structure not only significantly improves the firmness and mechanical properties of the material, but also enhances its stability, so that PTBA exhibits good elasticity, fatigue resistance and high strength.

[0021] The present invention utilizes the sunlight capture effect of nano-carbon black particles and vertical channel structure to show remarkable photothermal performance. Specifically, the microporous cavities are densely arranged on the surface, inducing continuous internal reflection of the incident light along the vertical channel. Subsequently, the interaction between the light and the nano-carbon black particles deposited on the pore wall is enhanced, thereby improving the light absorption efficiency. At 1 sun intensity (0.1W / cm 2 ) light, the surface temperature of PTBA can rise from the initial 25℃ to 71.6℃.

[0022] The PTBA of the present invention exhibits excellent adsorption and cleaning performance by virtue of its super hydrophobicity and super oleophilicity, unique pore structure and excellent mechanical properties. Even after repeated use, the PTBA can still maintain good absorption and separation capabilities and also exhibits excellent cleaning effects on high-viscosity crude oil.

[0023] The present invention studies the stability of PTBA in an organic solvent environment. PTBA was immersed in a n-hexane solution for 120 hours, and its water contact angle was measured after the solvent was completely volatilized. The results showed that the water contact angle of the treated PTBA surface remained above 150°, indicating that the aerogel has excellent solvent resistance.

[0024] The present invention investigates the applicability of PTBA in different environments and studies the effects of HCl, NaOH and NaCl solutions on its surface wettability. The results show that after being immersed in 1M NaCl solution for up to 36 hours, the water contact angle of PTBA is still stable at more than 149°, indicating that it has good salt resistance and reliability in the marine environment. Similarly, after being immersed in 1M HCl and NaOH solutions for up to 36 hours, the water contact angle of PTBA is still stable at more than 148°, indicating that it has excellent corrosion resistance in extreme acid and alkali environments. In summary, PTBA exhibits good tolerance and stability in various extreme environments.

[0025] The present invention investigates the repeated oil absorption performance of PTBA. The experimental results show that after 100 cycles of compression, the basic shape of PTBA hardly changes. Even after 10 cycles of absorption-release, the absorption rate of PTBA for ethylene dichloride is still over 97%. This shows that PTBA has excellent oil absorption capacity and good recyclability.

[0026] Through the preparation method of the present invention, PTBA can effectively adsorb high-viscosity crude oil floating on the water surface within 6 minutes by utilizing the photothermal effect and the capillary action of directional pores, and still maintain stable adsorption capacity after extrusion. In addition, during the extrusion process, the nano carbon black particles will not fall off. For dichloroethane deposited under water, PTBA also exhibits the characteristics of rapid absorption, which further highlights its excellent absorption and separation performance.

[0027] The present invention observed the continuous cleaning process of high-viscosity oil spills on the sea surface by PTBA with the assistance of a peristaltic pump through a camera. The results showed that within 6 minutes, 17 mL of high-viscosity crude oil was transferred to an empty beaker, and no seawater was mixed into it. This shows that PTBA has the characteristics of selectivity and efficiency in cleaning up oil spills on the sea surface, providing a new idea for cleaning up crude oil spills.

[0028] The present invention is based on the super oleophilicity, high porosity, good flexibility and super hydrophobicity / super oleophilicity of PTBA to water / oil, and is suitable for demulsification of water-in-oil (W / O) emulsions stabilized by surfactants. Since its porosity is as high as 98.8% and the heat transfer rate of air resistance is low, PTBA has good thermal insulation performance. With cellulose and chitosan as raw materials, PTBA not only has flame retardant properties and biodegradability, but also can realize the cleaning of oil spills in extreme environments, while greatly reducing the burden on the environment.

[0029] In summary, the PTBA of the present invention exhibits excellent performance and broad application prospects in the field of oil-water separation, and provides a convenient and effective solution for environmental protection and resource recovery.

[0030] The present invention has the following beneficial effects due to the adoption of the above technical solution:

[0031] The PTBA of the present invention uses cellulose and chitosan extracted from waste cartons as an organic skeleton, is chemically cross-linked by glutaraldehyde, and introduces nano carbon black particles as a photothermal component. In addition, methyltrimethoxysilane is used to hydrophobically modify it. The aerogel has excellent pore structure, super hydrophobicity-super oleophilicity and excellent mechanical properties, and exhibits excellent cleaning ability for high-viscosity crude oil. At the same time, the aerogel is reusable and biodegradable, which significantly reduces the burden on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the preparation process and chemical reaction mechanism of PTBA of the present invention;

[0033] Figure 2 The wetting behavior of oil and water on the surface of PTBA of the present invention and its ultra-light property (a), SEM image of PTBA cross section (b), SEM image of PTBA longitudinal section (c), and element distribution on the surface of PTBA (d);

[0034] Figure 3 The wettability changes of PTBA of the present invention after being soaked in n-hexane (a), and the wettability changes of PTBA after being soaked in acid, alkali, and salt solutions (b);

[0035] Figure 4 The infrared temperature measurement diagram of the photothermal effect of PTBA of the present invention and the control group (aerogel without photothermal particles introduced) is compared (a), the schematic diagram of the photothermal mechanism of PTBA and the SEM image of the distribution of nano carbon black particles on the surface (b), and the state of crude oil droplets on the surface of PTBA and the control group under light (c);

[0036] Figure 5 is the stress-strain curve of PTBA of the present invention subjected to 100 cycles of compression under 70% strain;

[0037] Figure 6 Figure 1 is a graph showing the adsorption of oils of different densities by PTBA of the present invention and an image of underwater oil recovery (a), and a graph showing the absorption-release of 10 cycles of ethylene dichloride by PTBA (b);

[0038] Figure 7 The PTBA of the present invention adsorbs the crude oil layer floating on the water surface under light (a), and the PTBA continuously recovers the crude oil on the water surface with the assistance of a peristaltic pump (b);

[0039] Figure 8 Schematic diagram of demulsification of water-in-oil (W / O) emulsion by PTBA of the present invention and optical images of emulsion and filtrate (a), water rolling angle in PTBA oil environment (b), schematic diagram of demulsification mechanism of W / O emulsion by PTBA (c), and particle size distribution diagram of emulsion before and after demulsification (d);

[0040] Fig. 9 The figures are flame retardant effect of PTBA of the present invention in a fire environment (a), heat insulation effect of PTBA on a heating table (b), heat insulation effect of PTBA on ice (c), degradation of PTBA without oil absorption in soil (d), FTIR spectrum comparison before and after PTBA degradation (e), and degradation of PTBA adsorbed and extruded crude oil in soil (f). DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and preferred embodiments. However, it should be noted that many details listed in the specification are only for the purpose of enabling the reader to have a thorough understanding of one or more aspects of the present invention, and these aspects of the present invention can be implemented even without these specific details.

[0042] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0043] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0044] Materials used in the following examples: Waste cartons (WCB) were collected from the office of Guangxi University (express paper packaging boxes). Chitosan (CS), sodium hydroxide (NaOH), methyltrimethoxysilane (MTMS), n-hexane, dichloroethane and kerosene were purchased from Shanghai McLean Biochemical Co., Ltd. Sodium hypochlorite (NaClO), acetic acid (HAc), and hydrochloric acid (HCl) were purchased from Chengdu Cologne Chemical Co., Ltd. Glutaraldehyde (GA) was purchased from Aladdin Reagent (Shanghai) Co., Ltd. Nanocarbon black particles (CB) were purchased from Guangdong Candlelight New Energy Technology Co., Ltd. Span 80 was purchased from Tianjin Fuchen Chemical Reagent Factory (China). Diesel and engine oil were obtained from local gas stations. Peanut oil was purchased from the local market. Crude oil (viscosity 1.38×10 5 mPa·s, 20°C) was obtained from Bohai Bay Station 2. Seawater was collected from Bohai Sea, China. Deionized water was used throughout the experiment. All chemical reagents were used as received without further purification.

[0045] Characterization methods used in the following examples: Scanning electron microscope (SEM, Merlin, Zeiss EVO-10) and energy dispersive x-ray (EDS) spectrometer were used to observe the sample morphology and element distribution. The water contact angle (WCA) and rolling angle (RA) on the sample surface were measured using a contact angle meter (OCA20, Data Physics ES, Germany). The temperature of the sample surface was measured using an infrared thermal imager (Uti320E). The mechanical properties of the sample were tested using an electronic universal testing machine (UTM2502, Shenzhen Sun Technology Co., Ltd., China) at a room temperature compression speed of 5 mm / min. The sample thickness was measured using a flat-head thickness gauge (Shenzhen Yuanhengtong Technology Co., Ltd.). A simulated sunlight lamp (ULTRA-VITALUX, Osram) was used to simulate sunlight. The mass and oil absorption of the sample were measured using an electronic balance ME204T / 02. The W / O emulsion was optically imaged and analyzed using an ultra-depth-of-field three-dimensional microscope system (VHX-700, Keyence (China) Co., Ltd.).

[0046] Example 1

[0047] Preparation and characterization of PTBA

[0048] 1. Preparation of PTBA

[0049] The preparation process of PTBA is as follows Figure 1 As shown, it is mainly divided into the following steps:

[0050] 1. Cellulose (CL) extraction

[0051] First, the recycled waste cartons were crushed with a high-speed grinder, and the powdered WCB was boiled in a 4% NaOH solution for 1 hour and mechanically stirred at 800 rpm for 6 hours to remove hemicellulose. The mixture was then filtered with a polyamide (PA) filter cloth and washed with deionized water until neutral. The resulting mixture was then stirred in a 2% NaClO solution for 3 hours to remove lignin, filtered and washed thoroughly with deionized water. Finally, the mixture was ultrasonically dispersed in deionized water to obtain a 0.5% concentration of cellulose suspension for use.

[0052] 2. Preparation of CL / CS composite solution

[0053] First, CS powder was vigorously stirred in 1% HAc solution at 60°C for 1h to obtain 0.5wt% CS solution. Then, the above CL suspension and CS solution were mixed in equal volumes to obtain 100ml of mixed solution, 0.1g of nano carbon black was added, and the mixture was vigorously stirred for 1h to obtain a uniform black solution. Subsequently, GA (4wt% CS powder) was added and stirred continuously in a 60°C water bath for 1h to allow continuous interaction between CL, CS and GA molecules. After cooling to room temperature, 0.6ml MTMS aqueous solution was added and mechanically stirred for 2h to obtain a siliconized composite solution. The preparation method of MTMS solution is as follows: in a pH=4 HCl solution, an equal volume of MTMS was added dropwise, mechanically stirred for 10min, and cooled to room temperature.

[0054] 3. Preparation of PTBA

[0055] Directional freezing technology was used to construct CL / CS composite aerogels with highly ordered anisotropic structures. A PMMA mold consisting of four sides was placed on a semiconductor refrigeration platform. The mixture was then poured into the mold and directionally frozen at -20°C for 40 minutes. Freeze-dried in a freeze dryer at -50°C and vacuum 1Pa for 48 hours. The freeze-dried aerogel was cross-linked in an oven at 110°C for 2 hours to obtain PTBA.

[0056] 2. Characterization of PTBA

[0057] The average density, average pore size and porosity of the PTBA prepared in this example are approximately 11 mg / cm 3 , 100μm and 98.8%. PTBA is as follows Figure 2 As shown in (a), a 30×30×20 mm PTBA is placed on the surface of the flower. The flower can fully support the entire aerogel without bending, indicating the low density of PTBA. The microstructure of PTBA was analyzed using a scanning electron microscope. Figure 2As shown in (b) and (c), the internal microstructure of PTBA presents a honeycomb structure in the horizontal direction. Each pore is composed of thin walls, forming a good connection between the fiber and the aerogel matrix, which helps to improve the overall performance of the aerogel. In the vertical direction, it presents a parallel pore structure. The regular and orderly directional pore structure runs through the upper and lower surfaces of the aerogel, forming a micron-scale pore array. These pore arrays can effectively enhance the capillary action of PTBA, realize directional transport behavior, and provide a stronger driving force for liquid transport. The surface chemical composition was measured by EDS, and C, O, and Si elements were detected on the surface of the internal channel ( Figure 2 (d)). Among them, the Si element with the largest atomic concentration is uniformly distributed on the entire surface, demonstrating the successful hydrophobic modification of MTMS.

[0058] Example 2

[0059] Superhydrophobicity of PTBA

[0060] Figure 2 (a) shows the wetting behavior of water and oil on the PTBA surface. Water droplets on the surface of PTBA are spherical and no penetration occurs, while n-hexane oil droplets quickly penetrate into the interior of PTBA. After measurement, the contact angle of water droplets on the PTBA surface is about 152.7°, and the rolling angle is about 8°. These results reveal the superhydrophobicity-superoleophilicity of the PTBA surface, showing excellent oil-water recognition properties. Based on its superhydrophobicity, when PTBA is immersed in a water environment, its surface shows a significant silver mirror effect.

[0061] The reason why PTBA is hydrophobic is that MTMS undergoes a dehydration reaction and polymerization to form a long silane chain, which reacts with the hydroxyl-OH in CL to form a water-repellent polymethylsiloxane. The formation of a hydrophobic film with methyl groups on the surface of the aerogel reduces the surface energy, making it impossible for water to enter. The entire reaction process involves multiple steps, including the hydrolysis, polymerization and film formation of organosilicon compounds, which work together to lead to the hydrophobicity of the aerogel. After further introduction of nano-carbon black particles, a hierarchical rough structure is constructed on the pore structure formed by directional freezing. These nano-scale particles combined with the micron-scale structure enhance the interface effect between the solid and the gas, thereby significantly reducing the surface area of ​​contact between the droplets and the particles. This structural regulation promotes the formation of the Cassie state, resulting in low adhesion of the droplets on the solid surface, which is also a key factor in the super-hydrophobicity of PTBA. In addition, through the mapping of element distribution analysis, it can be found that C, O and Si elements are densely distributed in the aerogel skeleton structure. Among them, the distribution of Si elements is more uniform and dense. It is precisely because of the low surface energy and the construction of multi-level rough structures that the PTBA surface exhibits extremely low liquid adhesion.

[0062] The applicability of PTBA in different environments was further investigated, and the effects of 1M HCl, NaOH and NaCl solutions and oil environments on its surface wettability were studied. The results showed that after immersion in n-hexane for 120 hours, the water contact angle of the PTBA surface remained stable at more than 150° ( Figure 3 (a)); After immersion in NaCl solution for up to 36 hours, the water contact angle of PTBA surface is still stable above 149°, indicating its salt resistance and reliability in marine environment; while after immersion in HCl and NaOH solution for up to 36 hours, the water contact angle of PTBA surface is still stable above 148°, indicating its corrosion resistance in extreme acid and alkali environment ( Figure 3 (b)). In summary, the PTBA of the present invention exhibits good tolerance and stability in various extreme environments.

[0063] To sum up, PTBA exhibits good tolerance, hydrophobicity and stability in various extreme environments. This excellent performance not only makes it widely applicable to various practical application scenarios, but also provides an effective solution to solving challenging problems.

[0064] Example 3

[0065] Photothermal properties of PTBA

[0066] The present invention utilizes the capture effect of nano carbon black (CB) and vertical pore structure on sunlight to show remarkable photothermal performance. Photothermal schematic diagram and the large amount of CB distributed on the pore wall are shown in the figure. Figure 4 (b). Specifically, the microporous cavities are densely arranged on the surface, inducing continuous internal reflection of the incident light along the vertical channel. Subsequently, a strong interaction occurs between the light and the CB deposited on the pore wall, thereby enhancing the absorption of light. The atoms and molecules inside the CB gain additional energy after absorbing light energy, intensifying their thermal vibrations. This thermal vibration further promotes the transfer and dissipation of energy, causing the particle temperature to increase and release thermal energy through interaction with the surrounding environment. Experiments show that at an intensity of 1 sun (0.1W / cm 2 ) under the illumination of the photothermal particles, the surface temperature of PTBA rose rapidly from the initial 25.1℃ to 71.6℃ within 120s, while the surface temperature of the control group (aerogel without the introduction of photothermal particles) only rose from the initial 25.3℃ to 37.5℃ ( Figure 4 (a)). At room temperature, crude oil was dropped on the surface of the aerogel, which showed a clear paste. After 2 minutes of illumination, the crude oil droplets quickly penetrated into the interior of the PTBA, while even after 5 minutes of illumination, the crude oil droplets remained on the surface of the control group ( Figure 4 (c)). This shows that under the combined effect of nano-carbon black and vertical pore structure, PTBA has a significant photothermal effect and can effectively accelerate the adsorption of high-viscosity crude oil.

[0067] Example 4

[0068] Mechanical properties of PTBA

[0069] The present invention selects cellulose (CL) and chitosan (CS) with long-chain structures as matrix materials, performs chemical cross-linking through glutaraldehyde (GA), and uses methyltrimethoxysilane (MTMS) for hydrophobic modification to construct PTBA. During the directional freezing process, CL and CS solutes form a vertical wall structure under the extrusion of ice crystals, which is converted into a vertical pore structure after freeze-drying. This structure significantly improves the overall firmness, mechanical properties and stability of PTBA, making it exhibit good elasticity, fatigue resistance and high strength. MTMS reacts on the surface to form a polymethylsiloxane layer, which is crucial to the overall firmness and stability of PTBA. Mechanical property tests show that when a 70% strain is applied perpendicular to the pore direction, the stress-strain curve of PTBA is as follows Figure 5 As shown. The maximum stress of PTBA is 10.2 kPa. In addition, PTBA exhibits minimal plastic deformation and retains 94% of the stress after 100 cycles of compression at 70% strain, showing excellent fatigue resistance. This excellent resilience is attributed to the anisotropy generated by the special vertical pore structure of PTBA. The precisely arranged vertical pores can effectively disperse stress (see Figure 5 illustration).

[0070] In summary, PTBA not only has good elasticity, fatigue resistance and high strength, but also has excellent stability and reliability. It can show excellent performance in different engineering and material applications, and provide reliable solutions for various challenging environments and applications.

[0071] Example 5

[0072] Oil absorption performance of PTBA

[0073] The oil adsorption capacity and repeated absorption-desorption performance of oil-water separation materials are key factors in evaluating their application value. Studies have found that PTBA can adsorb 58 to 123 times its own weight on oils and organic solvents of different densities. Figure 6 (a) is shown. For example, for a density of 0.83 g / cm 3 For crude oil with a density of 1.24 g / cm 3 The adsorption mass of ethylene dichloride can reach 123g / g. In addition, PTBA also exhibits the characteristic of rapid absorption of ethylene dichloride deposited under water, further demonstrating its separation performance for high-density oil and water (see Figure 6 (a) Illustration).

[0074] In terms of reusability, even after 10 absorption-release cycles, the absorption rate of PTBA for ethylene dichloride is still over 97% (see Figure 6 (b)). This indicates that PTBA not only has excellent oil absorption capacity but also has good recyclability.

[0075] Example 6

[0076] Application of high viscosity crude oil recovery

[0077] Based on the super hydrophobicity, vertical pore structure, photothermal performance and good mechanical properties of PTBA, it becomes an ideal material with excellent high viscosity crude oil adsorption performance. Figure 7 As shown in (a), at 1 sun intensity (0.1 W / cm 2 ) light, PTBA can effectively adsorb high-viscosity crude oil floating on the water surface in just 6 minutes and maintain stable adsorption capacity after squeezing. In addition, no particles fall off during the oil squeezing process, thus avoiding contamination of the recovered spilled oil. Figure 7 As shown in (b), the continuous recovery process of high-viscosity oil spills on the seawater surface by PTBA with the assistance of a peristaltic pump was observed by a camera. At room temperature, due to the extremely high viscosity of crude oil, it appears as a paste on the water surface. In the absence of light, low-density PTBA can be easily placed on its surface and remain stable. However, when the simulated solar lamp was turned on for 2 minutes, the crude oil was affected by the photothermal heating of PTBA, the fluidity increased, and was gradually adsorbed by PTBA. Within 6 minutes, 17 mL of crude oil was transferred to an empty beaker without seawater.

[0078] The above results show that PTBA is selective, efficient and self-absorbed when cleaning up oil spills on the sea surface, providing a new idea for crude oil spill cleanup.

[0079] Example 7

[0080] Demulsification performance of PTBA

[0081] Due to the super oleophilicity of PTBA, once it is immersed in an oil environment, a layer of oil will quickly fill the gaps in the micro-nanostructures, thereby isolating the contact between water and PTBA. For example, when a 6 μL water droplet is released onto the PTBA surface in a n-hexane environment, the measured rolling angle is only 5°, showing its super hydrophobicity in an oil environment ( Figure 8(b)). Therefore, PTBA is suitable for demulsification of surfactant-stabilized water-in-oil (W / O) emulsions due to its high porosity, good flexibility and superhydrophobicity / superoleophilicity. In order to test the separation performance of PTBA on W / O emulsions, we prepared surfactant-stabilized water-in-oil emulsions: 0.02 g Span 80 and deionized water were mixed with crude oil, ethylene dichloride and n-hexane in a volume ratio of 1:19 (v / v), respectively, and ultrasonically treated for 1 hour. Subsequently, the PTBA was compacted and fixed in a syringe, and the emulsion was poured on the surface of the PTBA, and the W / O emulsion was separated under gravity. Figure 8 As shown in (a), by observing the demulsification process and comparing the emulsion image with the filtrate image, the three W / O emulsions all changed from a turbid and fuzzy state to a clear and transparent state. Figure 8 As shown in (c), the demulsification mechanism is as follows: Due to the super lipophilicity of PTBA (contact angle CA oil Close to 0°) and superhydrophobicity (contact angle CA>150°), when the W / O emulsion contacts it, the continuous oil phase quickly penetrates into PTBA, while the dispersed water droplets are intercepted by pores and vertical channels. In addition, due to the weak adhesion between the water droplets and PTBA, the adjacent small water droplets will merge into larger droplets, float to the upper surface and form a free water layer. At the same time, the clean oil passes through PTBA under the action of gravity and capillary force. Figure 8 As shown in (d), we measured the dispersion and corresponding particle size in the three emulsions. The results show that the water droplet size in the emulsion is about 1 μm, while the particle size distribution in the emulsifier is around 1 nm, which may be due to the residual surfactant in the emulsifier. These results show that PTBA has a significant effect on demulsification of surfactant-stabilized water-in-oil (W / O) emulsions.

[0082] Example 8

[0083] The application value of PTBA in thermal insulation, flame retardancy and biodegradability

[0084] like Fig. 9 As shown in (a), PTBA exhibits significant flame retardancy when exposed to flame. It can be clearly observed that only slight carbonization occurs on the burning surface, and there are nearly spherical blue water droplets on the surface. The water contact angle is about 145°, and it still maintains strong hydrophobicity. The flame retardancy of PTBA is mainly attributed to the following two points: on the one hand, chitosan (CS) undergoes a ring-opening reaction at high temperature to form an aromatic ring cross-linked structure and increase the degree of carbonization, thereby exhibiting good flame retardancy; on the other hand, CS releases NH and N during the combustion process, diluting the oxygen concentration to inhibit combustion. Due to the high porosity of 98.8%, PTBA has a low air resistance heat transfer rate and therefore has good thermal insulation properties. As Fig. 9As shown in (b), PTBA is placed on a heating stage with a surface temperature of 400°C. The infrared image shows the temperature distribution on the side of the PTBA. The temperature of the 1 cm thick PTBA drops from 400°C to 61.8°C from bottom to top, with almost no change within 30 minutes. In addition, Fig. 9 As shown in (c), 300 μL of water was dropped on PTBA with a thickness of 2 mm, and the PTBA was placed on an ice surface at -12°C. The surface temperature of the water drop was always close to the ambient temperature of 20°C, and during the 60-minute insulation test, the water showed no signs of freezing. In summary, PTBA shows potential flame retardant and thermal insulation value and has broad application prospects.

[0085] Imparting biodegradability to adsorbents can significantly reduce environmental burdens. Based on this, we buried oil-absorbed and non-oil-absorbed PTBA in soil environments to evaluate their degradability. Fig. 9 As shown in (d), after 10 days, a large number of pores and cracks visible to the naked eye appeared on the surface of the PTBA that had not absorbed oil, and gradually shrunk over time. After 30 days, the volume of PTBA was reduced to 1 / 3 of the original volume, indicating that its matrix skeleton began to collapse. By comparing the FTIR spectra of the original PTBA and the PTBA after 30 days of degradation ( Fig. 9 (e)), it was found that the peak intensity of COH bonds and CC bonds (the main chemical components of chitosan and cellulose) in the degraded PTBA was significantly reduced. In addition, the degraded PTBA lost its compressibility and was easily crushed by hand (see Fig. 9 (e) Illustration). Fig. 9 As shown in (f), PTBA adsorbed and squeezed by crude oil also showed similar morphological evolution, with a 30% volume reduction within 14 days of burial in soil environment. These changes in morphology and chemical composition demonstrate the degradability and environmental friendliness of PTBA.

[0086] The above results show that PTBA has the characteristics of simple preparation, low cost, environmental friendliness, reusability and high mechanical properties, and is selective and efficient in the cleanup process of oil spills on the sea surface, providing a new idea for crude oil spill cleanup. It has a significant effect on the demulsification of surfactant-stabilized water-in-oil (W / O) emulsions, and has great potential value in thermal insulation, flame retardancy and biodegradability.

[0087] In summary, PTBA has demonstrated excellent performance and broad application prospects in the field of oil-water separation, providing a convenient and effective solution for environmental protection and resource recovery.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a degradable photothermal aerogel with super hydrophobicity / super oleophilicity, characterized in that: The following steps are involved: (1) extracting cellulose from waste cartons and preparing a cellulose suspension by ultrasonic dispersion; (2) preparing chitosan solution; (3) mixing the cellulose suspension and the chitosan solution to obtain a cellulose / chitosan composite solution, adding nano carbon black particles, glutaraldehyde and methyltrimethoxysilane aqueous solution to the cellulose / chitosan composite solution, and stirring; (4) injecting the composite solution into a mold and performing directional freezing on a semiconductor refrigeration platform; (5) The frozen sample is freeze-dried and then placed in an oven for cross-linking to obtain an aerogel.

2. The method for preparing a degradable photothermal aerogel having super hydrophobicity / super oleophilicity according to claim 1, characterized in that: In step (1), the specific treatment process of the cellulose suspension is as follows: waste carton powder is treated with sodium hydroxide solution and sodium hypochlorite solution, washed with deionized water until neutral, then filtered, and ultrasonically dispersed to obtain a cellulose suspension; the concentration of the cellulose suspension is 0.5wt%.

3. The method for preparing a degradable photothermal aerogel having super hydrophobicity / super oleophilicity according to claim 1, characterized in that: In step (2), the specific process of preparing the chitosan solution is: adding chitosan powder to 1% acetic acid solution, and vigorously stirring for 1 hour at a temperature of 60° C. to obtain a chitosan solution; the concentration of the chitosan solution is 0.5wt%.

4. The method for preparing a degradable photothermal aerogel with super hydrophobicity / super oleophilicity according to claim 1, characterized in that: In step (3), the mass ratio of the nano carbon black particles to the cellulose is 0.1:1, the mass ratio of the glutaraldehyde solution to the chitosan is 0.04:1, and the volume ratio of the methyltrimethoxysilane solution to the total solution is 0.6:

100.

5. The method for preparing a degradable photothermal aerogel with super hydrophobicity / super oleophilicity according to claim 1, characterized in that: In step (4), the specific conditions of the directional freezing are as follows: the surface temperature of the semiconductor refrigeration platform is -20°C, and the directional freezing is carried out at room temperature; in step (5), the freeze dryer is set to -50°C, 1Pa; the cross-linking temperature is 110°C, and the time is 2h.

6. A degradable photothermal aerogel having super hydrophobicity / super oleophilicity prepared according to the method according to any one of claims 1 to 5.

7. Use of the degradable photothermal aerogel with super hydrophobicity / super oleophilicity according to claim 6 in oil-water separation.

8. A method for oil-water separation, comprising the step of using the degradable photothermal aerogel with super hydrophobicity / super oleophilicity as claimed in claim 6 as an oil-water separation material for separation.

9. The method for oil-water separation according to claim 8, characterized in that: The super-hydrophobic / super-oleophilic degradable photothermal aerogel realizes oil-water separation by absorption separation.

10. The method for oil-water separation according to claim 8 or 9, characterized in that: When performing absorption separation, the degradable photothermal aerogel with super hydrophobicity / super oleophilicity adsorbs the diffused high-viscosity crude oil.

Citation Information

Patent Citations

  • Method for preparing magnetic cellulose aerogel by utilizing waste paper

    CN106589444A

  • Preparation method of waste paper based recoverable aerogel used for oil-water separation

    CN108686628A

  • Structurally ordered chitosan / nanocellulose composite aerogel and preparation method thereof

    CN111195508A

  • Super-hydrophobic chitosan hybrid aerogel and preparation method thereof

    CN115124760A

  • Cellulose / chitosan magnetic composite material as well as preparation method and application thereof

    CN116769225A

Cited By

  • Waste corrugated paper / bentonite aerogel as well as preparation method and application thereof

    CN120571565A

  • Hierarchical topological framework chitosan framework for zinc-based energy storage device and preparation method of hierarchical topological framework chitosan framework

    CN120690859A

  • Hydrophobic nanocellulose / graphene / polyurea aerogel as well as preparation method and application thereof

    CN121699234A

  • Multifunctional aerogel film based on charge demulsification, preparation method and application

    CN122076396A